PEMBERDAYAAN MASYARAKAT MELALUI KELOMPOK USAHA TANI KOPI NAGARI KOTO HILALANG - Fera Zora; Helvita Roza; Arfimasri Arfimasri; Intan Putri Delima; Adinda Putri Ellia (ASOSIASI IDEBAHASA KEPRI, 2026)
This community service program aims to improve the institutional capacity and business management capabilities of the Nagari Koto Hilalang Coffee Farmers Group. The program was implemented in several stages: outreach to partners and stakeholders on May 18, 2025, business management and financial literacy training on May 23, 2025, and post-harvest coffee processing training on June 6, 2025. Methods used included lectures, discussions, demonstrations, and hands-on practice. The business management training materials covered business planning, organization, simple financial record keeping, and group institutional restructuring. The results of the program demonstrated an increase in group members' understanding of business governance, financial record keeping, and post-harvest coffee handling techniques, which is expected to improve the quality and economic value of the coffee produced. This activity also strengthened the synergy between the farmer group and stakeholders in supporting sustainable coffee business development. Keywords: Community Empowerment, Coffee, Post-Harvest, Farmer Group, Business Management.